Analisis Pengendalian Kualitas Produk Compound Dengan Model Seven Tools Di PT Velasto Indonesia - Sutartiah, Farliana; Zamal , Raqib; Putri, Pandena Kicky Basuki (Jurnal Teknologika, 2025)
This study focuses on quality control using the QC Seven Tools method to reduce product defects in compound production at PT Velasto Indonesia, located in Purwakarta Regency. Defective products can lead to increased production costs, decreased customer satisfaction, and reduced competitiveness. Therefore, identifying the root causes of defects and implementing effective control measures are essential. The QC Seven Tools—comprising Check Sheets, Histograms, Pareto Diagrams, Cause-and-Effect Diagrams, Control Charts, Scatter Diagrams, and Flowcharts—are applied to analyze and monitor the production process. This study uses primary data collected from direct observations, interviews with production staff, and company production records. Analysis using the Pareto Diagram revealed that the most frequent defects in compound products were surface roughness, inconsistent texture, and contamination. The Cause-and-Effect Diagram identified potential root causes such as machine malfunctions, operator error, and inconsistent raw material quality. Control Charts were utilized to observe process stability, while Scatter Diagrams helped identify correlations between variables affecting quality.The results showed that implementing corrective actions based on QC tool analysis—such as machine maintenance scheduling, operator training, and supplier quality control—led to a significant reduction in defect rates. This demonstrates that the QC Seven Tools are effective in identifying, analyzing, and resolving quality issues in manufacturing processes. Overall, this study highlights the importance of structured quality control approaches in achieving continuous improvement and operational efficiency. The findings provide practical insights for other manufacturing companies aiming to minimize defects and improve product quality through systematic problem-solving techniques.